Criteria for developing communication skills of internal affairs officers in their relations with the public - Jahangir Ismailov (Zien Journals, 2026)
Another characteristic feature of the professional activity of internal affairs officers in ensuring the stability of society is their ability to interact with a wide range of environments. The activity of ensuring a culture of communication is of great importance in the professional competence of an internal affairs officer.
Keywords: Society; social stability; public order